Desde as marcas que carrego fico pensando: como a escola educa, mas também fere? - Oliveira, Josiane Cristina de (Universidade Federal de São Carlos, 2019)
The object of this research was born from my experiences in the Supervised Internship in Early Childhood Education held in 2013 at a municipal school in the city of Votorantim / SP, which motivated the desire to investigate the possible consequences of relationships permeated by various types of violence that can occur inside the school. The research aimed to understand how the power relations between teacher and child are built in the school environment, as well as to investigate the marks left in the life of the child who experiences oppression and restrictions on his way of being a child. The research is qualitative and bibliographic. The main authors that support the work are: Michel Foucault (1987), Cláudia Rennó (2009), Adriana Rasera (2010) e Jucilaine Zucco (2008). They cover the subjects of discipline, body, authority and power, helping to understand the dynamics of these concepts when they are present at school. The work is divided into four chapters. The first chapter presents the construction of my Memorial, in which I reflect on my personal history in which it may have relations with the research, making a journey until I reach the course of Pedagogy. The second chapter presents the theoretical framework. The third chapter reports the methodology and the fourth presents the analysis of the data that were collected in the field, during the internship. The results reveal that the relations of power and authority within the school are influenced by values coming from a society marked by discipline and the need to adapt to a longing for production and work processes.
From the marks I carry I wonder: how does school educate, but also hurt?
Keywords: Disciplina; Poder; Escola; Discipline; Power; School; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO